Molecular and genetic targets within metastatic colorectal cancer and associated novel treatment advancements - Cann, Christopher G.; LaPelusa, Michael B.; Cimino, Sarah K.; Eng, Cathy (Frontiers in Oncology, 2023)
Colorectal cancer results in the deaths of hundreds of thousands of patients worldwide each year, with incidence expected to rise over the next two decades. In the metastatic setting, cytotoxic therapy options remain limited, which is reflected in the meager improvement of patient survival rates. Therefore, focus has turned to the identification of the mutational composition inherent to colorectal cancers and development of therapeutic targeted agents. Herein, we review the most up to date systemic treatment strategies for metastatic colorectal cancer based on the actionable molecular alterations and genetic profiles of colorectal malignancies.